High-toughness concrete decorative brick as well as preparation method and application thereof
By introducing nanoclay and modified fiber reinforced polypropylene into concrete decorative bricks, the problem of insufficient tensile strength and fracture toughness of existing concrete decorative bricks is solved, and the high toughness and crack resistance are improved, which is suitable for the preparation of decorative walls or floors.
Patent Information
- Application Number
- CN202510203049.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-24
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2045-02-24
AI Technical Summary
Existing concrete decorative bricks have shortcomings in tensile strength and fracture toughness, especially in wet or chloride environments, where fibers such as steel fibers are prone to corrosion and affect their performance.
High tough concrete decorative bricks are prepared by introducing nanoclay and modified fiber reinforced polypropylene into the concrete. Nanoclay improves the mechanical properties and toughness of concrete, modified fiber-reinforced polypropylene improves tensile strength and fracture toughness, and enhances the mechanical properties of the material through the addition of potassium feldspar powder.
It has achieved significant improvements in tensile strength and fracture toughness of high-tough concrete decorative bricks, which are suitable for the preparation of decorative walls or floors, and exhibits good crack propagation and chemical corrosion resistance in humid environments.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of concrete, and in particular to a high-toughness concrete decorative brick and a preparation method and application thereof. Background Art
[0002] Concrete is a common building material. According to the usage requirements of the application scenario, the corresponding functional requirements can be achieved through concrete formula design.
[0003] For common decorative walls and floors, concrete needs to be prepared into decorative bricks. The decorative bricks need to form ornamental colors, textures and patterns on their surfaces. They are required to have high tensile strength, fracture toughness and impermeability resistance. For decorative bricks used for exterior wall decoration, they are also required to have good resistance to crack propagation. For other decorative bricks such as floors that need frequent cleaning, they are also required to have good resistance to chemical corrosion.
[0004] In the existing technology, high-performance fibers (such as steel fibers) are mainly introduced into concrete for modification to improve the tensile strength and crack resistance of concrete, which is more adaptable in scenes that need to withstand large loads and impacts. However, for the concrete used in decorative tiles, not only high tensile strength is required, but also high fracture toughness is required; and some decorative walls and floors will be used in humid environments, and fibers such as steel fibers are easily corroded, especially in humid or chloride ion environments. Summary of the invention
[0005] The object of the present invention is to provide a high-toughness concrete decorative brick having both high tensile strength and fracture toughness.
[0006] In addition, the present invention also provides a preparation method and application of the high-toughness concrete decorative brick.
[0007] The present invention is achieved through the following technical solutions: A high-toughness concrete decorative brick comprises the following components in parts by weight: 500-600 parts of cement, 120-150 parts of nano clay, 80-100 parts of modified fiber reinforced polypropylene, 1000-1200 parts of aggregate, 3-5 parts of water reducer, 100-200 parts of water; The fibers used in the modified fiber reinforced polypropylene are glass fibers and carbon fibers; the polypropylene used in the modified fiber reinforced polypropylene is maleic anhydride grafted polypropylene, and potassium feldspar powder is added to the maleic anhydride grafted polypropylene; Wherein, the nano clay is a mixture of bentonite powder and potassium feldspar powder; Wherein, the potassium feldspar powder is modified potassium feldspar powder; the preparation process of the modified potassium feldspar powder is as follows: Potash feldspar powder and activated carbon powder are mixed for 30-60 minutes, wherein the particle size of the activated carbon powder is smaller than that of the potash feldspar powder, and then the activated carbon powder is removed by sieving, and then the potash feldspar powder is mixed with smithsonite powder and calcium carbonate powder and ball milled for 30 minutes, wherein, based on the weight of the potash feldspar powder, the amount of smithsonite powder is 10%, the amount of activated carbon powder is 5%, and the amount of calcium carbonate powder is 8%.
[0008] The present invention introduces nano clay and modified fiber reinforced polypropylene on the basis of existing concrete to prepare high-toughness concrete decorative bricks; wherein, nano clay is a nano-scale filler, which can improve the mechanical properties of concrete, and the nano clay is evenly dispersed in the concrete, which can effectively prevent cracks from expanding, thereby improving the toughness of concrete. Among them, the modified fiber reinforced polypropylene can improve the toughness and tensile strength of concrete, and can effectively disperse external stress, reduce stress concentration inside the concrete, thereby preventing cracks from expanding, and can also improve the density of concrete and effectively reduce the penetration of moisture and chemical substances. The fiber used in the modified fiber reinforced polypropylene of the present invention is a composite fiber (mixed fiber) of glass fiber and carbon fiber, which can improve the toughness and tensile strength of concrete compared with the single use of glass fiber; maleic anhydride grafted polypropylene is used as a resin, which can improve the toughness of concrete compared with the direct use of polypropylene, and potassium feldspar powder is introduced into the maleic anhydride grafted polypropylene, and the potassium feldspar powder contains potassium, has a certain interlayer stability, is not easy to expand, can improve the mechanical properties of maleic anhydride grafted polypropylene, and can improve the tensile strength and toughness of the modified fiber reinforced polypropylene.
[0009] Bentonite powder is a kind of substance that can absorb water and become a gel-like substance. When the gel-like substance formed by bentonite powder is dispersed in concrete, it can improve the toughness and density of concrete. Among them, potassium feldspar powder contains potassium, has a certain interlayer stability, and is not easy to expand. Mixing bentonite powder and potassium feldspar powder can further improve the toughness and density of concrete.
[0010] Among them, when potassium feldspar powder is modified with activated carbon powder, smithsonite powder and calcium carbonate powder, the tensile strength and toughness of concrete can be further improved. Among them, activated carbon has a very high specific surface area and strong adsorption capacity, and can effectively adsorb harmful impurities and pollutants in potassium feldspar powder, thereby improving the purity and quality of potassium feldspar powder, and further improving the activity of potassium feldspar powder. Smithsonite powder and calcium carbonate powder are used as additives to further improve the activity of potassium feldspar powder. Ball milling potassium feldspar powder, smithsonite powder and calcium carbonate powder together can improve the surface activity of potassium feldspar powder, smithsonite powder and calcium carbonate powder on the one hand, which is conducive to zinc ore powder and calcium carbonate powder as additives to modify high potassium feldspar powder. On the other hand, it can improve the uniformity of mixing potassium feldspar powder, smithsonite powder and calcium carbonate powder.
[0011] In summary, the present invention introduces nano clay and modified fiber reinforced polypropylene into concrete, so that the prepared high-toughness concrete decorative bricks have both high tensile strength and fracture toughness.
[0012] In a preferred embodiment, the weight ratio of bentonite powder to potassium feldspar powder is (3-4):1.
[0013] In a preferred embodiment, the preparation process of modified fiber reinforced polypropylene is as follows: Firstly, the glass fiber and the carbon fiber are surface treated with nano-silicon dioxide respectively, and then the surface treated glass fiber and carbon fiber are mixed, and then the mixed fiber is mixed with maleic anhydride grafted polypropylene, and then the modified fiber reinforced polypropylene is obtained by extrusion process.
[0014] In a preferred embodiment, the amount of potassium feldspar powder added to the maleic anhydride grafted polypropylene is 12-15% by weight.
[0015] Although adding a certain amount of potassium feldspar powder to maleic anhydride grafted polypropylene can improve the tensile strength and fracture toughness of concrete, when the potassium feldspar powder is added in too much amount, it will lead to the opposite effect.
[0016] In a preferred embodiment, the aggregate includes coarse aggregate and fine aggregate; the particle size of the coarse aggregate is (2.5-2.0) mm, and the particle size of the fine aggregate is (0.5-0.8) mm; the weight ratio of the coarse aggregate to the fine aggregate is 1:(0.5-0.6).
[0017] The packing density of aggregate affects the strength and density of concrete. By reasonably setting the particle size and weight ratio of coarse aggregate and fine aggregate, the strength and density of concrete can be improved, thereby improving the concrete's anti-permeability.
[0018] In a preferred embodiment, the high-toughness concrete decorative brick also includes 30-50 parts of mineral admixture; the mineral admixture is a mixture of fly ash and slag powder, and the weight ratio of fly ash to slag powder is (2-3):1.
[0019] The invention can improve the chemical corrosion resistance of the high-toughness concrete decorative bricks by simultaneously adding fly ash and slag powder into the high-toughness concrete decorative bricks.
[0020] In a preferred embodiment, the water-cement ratio of the high-toughness concrete decorative tiles is (0.20-0.25).
[0021] The water-cement ratio of concrete affects the density of concrete. When the water-cement ratio of concrete is too large, the density of concrete will be lower and its anti-permeability will be reduced.
[0022] A method for preparing a high-toughness concrete decorative brick comprises the following steps: S1. Preparation of modified fiber reinforced polypropylene: S11, firstly surface-treating the glass fiber and the carbon fiber respectively with nano-silicon dioxide; S12, mixing the glass fiber and the carbon fiber processed in step S11 at a weight ratio of 3:1, wherein the length of the glass fiber and the carbon fiber are both 15-20 mm; S13, dispersing the potassium feldspar powder in the maleic anhydride grafted polypropylene, then uniformly mixing the mixed fiber and the maleic anhydride grafted polypropylene, putting them into an extruder for extrusion molding, cooling, and pelletizing to obtain the modified fiber reinforced polypropylene; S2. Add cement, nanoclay, aggregate and water reducing agent in proportion into a forced mixer and dry mix at a speed of 35-45r / min for 3-4 minutes. Add water and fluidize and stir for 3-4 minutes. Add modified fiber reinforced polypropylene and continue stirring for 4-5 minutes to obtain concrete. Pour the concrete into a mold and cure it to obtain high-toughness concrete decorative tiles.
[0023] In a preferred embodiment, the weight ratio of the composite long glass fiber to the maleic anhydride grafted polypropylene in the modified fiber reinforced polypropylene is (2-3): (3-5); the amount of potassium feldspar powder added to the maleic anhydride grafted polypropylene is 12-15% based on the weight of the maleic anhydride grafted polypropylene.
[0024] The present invention uses nano-silicon dioxide to pretreat glass fibers and carbon fibers, thereby improving the roughness and hydrophobicity of the surfaces of glass fibers and carbon fibers, that is, making the connection between the glass fibers and carbon fibers and other components in concrete stronger, thereby ensuring the reinforcing effect of the fibers on maleic anhydride grafted polypropylene.
[0025] The invention discloses an application of high-toughness concrete decorative bricks, and the products used for preparing the same include decorative walls or floors.
[0026] Compared with the prior art, the present invention has the following advantages and beneficial effects: The present invention introduces nano clay and modified fiber reinforced polypropylene on the basis of existing concrete to prepare high-toughness concrete decorative bricks; wherein, nano clay is a nano-scale filler, which can improve the mechanical properties of concrete and effectively prevent crack propagation; modified fiber reinforced polypropylene can improve the toughness and tensile strength of concrete, so that the prepared high-toughness concrete decorative bricks have both high tensile strength and fracture toughness, and are particularly suitable for the preparation of decorative walls or floors. DETAILED DESCRIPTION
[0027] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with the embodiments. The schematic implementation mode of the present invention and its description are only used to explain the present invention and are not intended to limit the present invention. The embodiments described below are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.
[0028] In the following description, a large number of specific details are set forth in order to provide a thorough understanding of the present invention. However, it is apparent to those of ordinary skill in the art that these specific details do not have to be employed to practice the present invention. In other embodiments, in order to avoid confusing the present invention, known structures, materials or methods are not specifically described. The materials, instruments and reagents used in the following examples, unless otherwise specified, can be obtained from commercial sources. The technical means used in the examples, unless otherwise specified, are conventional means well known to those skilled in the art.
[0029] In order to improve the tensile strength and fracture toughness of concrete, this embodiment provides a high-toughness concrete decorative brick, including the following components in parts by weight: 500-600 parts of cement, 120-150 parts of nano clay, 80-100 parts of modified fiber reinforced polypropylene, 1000-1200 parts of aggregate, 3-5 parts of water reducer, 100-200 parts of water; The fibers used in the modified fiber reinforced polypropylene are glass fibers and carbon fibers; the polypropylene used in the modified fiber reinforced polypropylene is maleic anhydride grafted polypropylene, and potassium feldspar powder is added to the maleic anhydride grafted polypropylene; the amount of potassium feldspar powder added to the maleic anhydride grafted polypropylene is 12-15% by weight. Maleic anhydride grafted polypropylene is an existing technology, and a purchased product with a grafting rate of 1.1% and a melt index of 180g / 10min is preferably used; wherein the melt index is a flow rate tested under the conditions of 230°C and a load of 2.16kg. The preparation process of modified fiber reinforced polypropylene is as follows: Firstly, the glass fiber and the carbon fiber are surface treated with nano-silicon dioxide respectively, and then the surface treated glass fiber and carbon fiber are mixed in proportion, and then the mixed fiber is mixed with maleic anhydride grafted polypropylene, and then the modified fiber reinforced polypropylene is obtained by extrusion process.
[0030] The water reducer is preferably a polycarboxylate water reducer or a naphthalene water reducer. The polycarboxylate water reducer and the naphthalene water reducer can significantly reduce the water-cement ratio of the concrete while maintaining the slump of the concrete substantially unchanged, thereby improving the strength and durability of the concrete. The polycarboxylate water reducer and the naphthalene water reducer are both purchased.
[0031] Among them, cement is ordinary Portland cement.
[0032] Among them, nanoclay is nanoparticles of layered mineral silicates; such as montmorillonite, bentonite, halloysite nanoclay, etc.; in a preferred case, the nanoclay is a mixture of bentonite powder and potassium feldspar powder, wherein the weight ratio of bentonite powder to potassium feldspar powder is (3-4):1.
[0033] In a preferred case, the aggregate includes coarse aggregate and fine aggregate; the particle size of the coarse aggregate is (2.5-2.0) mm, and the particle size of the fine aggregate is (0.5-0.8) mm; the weight ratio of the coarse aggregate to the fine aggregate is 1: (0.5-0.6); in order to improve the density of the concrete, the aggregate can specifically be river sand, machine-made sand, etc.
[0034] In a preferred case, the water-binder ratio of the high-toughness concrete decorative brick is (0.20-0.25). A lower water-binder ratio can improve the density of the concrete, thereby improving its anti-permeability. The water-binder ratio is the ratio of water to gel material (the total weight of cement and nanoclay) in the high-toughness concrete decorative brick.
[0035] In a preferred case, the high-toughness concrete decorative brick also includes 30-50 parts of mineral admixtures; the mineral admixture is a mixture of fly ash and slag powder, and the mass ratio of fly ash to slag powder is (2-3):1. The composite of fly ash and slag can significantly improve the weakness of slag concrete in terms of poor chemical corrosion resistance. Among them, fly ash is the material discharged from the flue after the finely ground fly ash in the coal-fired power plant is burned in the boiler and collected by the dust collector. The main components are SiO2, Al2O3 and Fe2O3; slag powder is an industrial by-product produced in the iron smelting process, and the main components are CaO, SiO2 and Al2O3.
[0036] In a preferred case, the potassium feldspar powder is a modified potassium feldspar powder; the preparation process of the modified potassium feldspar powder is as follows: The potassium feldspar powder is mixed with the activated carbon powder for 30-60 minutes, wherein the particle size of the activated carbon powder is smaller than that of the potassium feldspar powder. The activated carbon powder has a smaller particle size and a larger specific surface area, and can better absorb impurities. Then the activated carbon powder is removed by screening, and the potassium feldspar powder is mixed with the smithsonite powder and the calcium carbonate powder and ball milled for 30 minutes. The amount of the smithsonite powder is 10%, the amount of the activated carbon powder is 5%, and the amount of the calcium carbonate powder is 8% based on the weight of the potassium feldspar powder. By modifying the potassium feldspar powder, the tensile strength and fracture toughness of the concrete can be further improved.
[0037] The method for preparing the high-toughness concrete decorative brick comprises the following steps: S1. Preparation of modified fiber reinforced polypropylene: S11. First, the glass fiber and carbon fiber are surface treated with nano-silicon dioxide respectively, and the single fiber diameters of the glass fiber and carbon fiber are both 15-20μm; the specific process is: prepare an aqueous solution containing nano-silicon dioxide by ultrasonic dispersion, and then immerse the glass fiber and carbon fiber in the aqueous solution containing nano-silicon dioxide respectively, specifically, mix nano-silicon dioxide powder and water in a weight ratio of 1:4, and perform ultrasonic treatment for 45 minutes, and use the surface tension of the fiber to make the nano-silicon dioxide particles adhere to the surface of the glass fiber and carbon fiber, which can enhance the surface roughness and affinity of the glass fiber and carbon fiber.
[0038] S12, mixing the glass fiber and carbon fiber processed in step S11 at a weight ratio of 3:1, wherein the length of the glass fiber and the carbon fiber are both 15-20 mm.
[0039] S13, dispersing potassium feldspar powder in maleic anhydride grafted polypropylene, and then uniformly mixing the mixed fiber and maleic anhydride grafted polypropylene; the addition amount of potassium feldspar powder in the maleic anhydride grafted polypropylene is 12-15% based on the weight of the maleic anhydride grafted polypropylene; the mass ratio of the mixed fiber to the maleic anhydride grafted polypropylene in the modified fiber reinforced polypropylene is 3: 5, and the mixed fiber is put into an extruder for extrusion molding, cooling, and pelletizing to obtain modified fiber reinforced polypropylene.
[0040] S2. Add cement, nanoclay, aggregate and water reducing agent in proportion into a forced mixer and dry mix at a speed of 35r / min for 4 minutes. Add water and fluidize and mix for 4 minutes. Add modified fiber reinforced polypropylene and continue mixing for 5 minutes to obtain concrete. Pour the concrete into a mold and perform conventional curing for 28 days to obtain high-toughness concrete decorative tiles.
[0041] The high-toughness concrete decorative brick prepared in this embodiment has both high tensile strength and fracture toughness, and is particularly suitable for the preparation of decorative walls or floors.
[0042] In order to better illustrate the effect of this embodiment, the following specific case is used for illustration.
[0043] Embodiment 1: A high-toughness concrete decorative brick, composed of the following components in parts by weight: 600 parts of ordinary Portland cement, 150 parts of nano clay, 100 parts of modified fiber reinforced polypropylene, 1200 parts of aggregate, 5 parts of polycarboxylate water reducer, and 180 parts of water.
[0044] In this embodiment, the water-to-cement ratio of the high-toughness concrete decorative brick is 0.24.
[0045] The nanoclay is obtained by mixing bentonite powder and potassium feldspar powder in a weight ratio of 4:1; The aggregate is machine-made sand, and the aggregate includes coarse aggregate and fine aggregate; the particle size of the coarse aggregate is (2.5-2.0) mm, and the particle size of the fine aggregate is (0.5-0.8) mm; the weight ratio of the coarse aggregate to the fine aggregate is 1:0.6; Wherein, in the process of preparing the modified fiber reinforced polypropylene, the addition amount of potassium feldspar powder in the maleic anhydride grafted polypropylene is 12% based on the weight of the maleic anhydride grafted polypropylene.
[0046] Embodiment 2: This embodiment is based on embodiment 1, and the difference from embodiment 1 is that the dosage of each component in the formula is different, as follows: A high-toughness concrete decorative brick, composed of the following components in parts by weight: 500 parts of ordinary Portland cement, 120 parts of nano clay, 80 parts of modified fiber reinforced polypropylene, 1000 parts of aggregate, 3 parts of polycarboxylate water reducer, and 150 parts of water.
[0047] In this embodiment, the water-to-cement ratio of the high-toughness concrete decorative brick is 0.24.
[0048] Embodiment 3: This embodiment is based on the embodiment 1, and the difference from the embodiment 1 is that the amount of potassium feldspar powder added in the modified fiber reinforced polypropylene is different, specifically: In the process of preparing modified fiber reinforced polypropylene, the addition amount of potassium feldspar powder in the maleic anhydride grafted polypropylene is 15% based on the weight of the maleic anhydride grafted polypropylene.
[0049] Embodiment 4: This embodiment is based on Example 1, and the difference from Example 1 is that 50 parts of mineral admixture are further added to the formula, as follows: A high-toughness concrete decorative brick, composed of the following components in parts by weight: 600 parts of ordinary Portland cement, 150 parts of nano clay, 100 parts of modified fiber reinforced polypropylene, 1200 parts of aggregate, 5 parts of polycarboxylate water reducer, 50 parts of mineral admixture, and 180 parts of water.
[0050] The mineral admixture is a mixture of fly ash and slag powder, and the mass ratio of fly ash to slag powder is 3:1.
[0051] Embodiment 5: This embodiment is based on Example 1, and the difference from Example 1 is that 30 parts of mineral admixtures are further added to the formula, as follows: A high-toughness concrete decorative brick, composed of the following components in parts by weight: 600 parts of ordinary Portland cement, 150 parts of nano clay, 100 parts of modified fiber reinforced polypropylene, 1200 parts of aggregate, 5 parts of polycarboxylate water reducer, 30 parts of mineral admixture, and 180 parts of water.
[0052] Embodiment 6: This embodiment is based on Embodiment 1, and the difference from Embodiment 1 is that the potassium feldspar powder in this embodiment adopts modified potassium feldspar powder, and the specific preparation process of the modified potassium feldspar powder is as follows: Potassium feldspar powder and activated carbon powder are mixed for 60 minutes, and the amount of activated carbon powder is 5% based on the weight of the potassium feldspar powder; wherein the particle size of the activated carbon powder is smaller than the particle size of the potassium feldspar powder, and then the activated carbon powder is removed by screening, and then the potassium feldspar powder is mixed with smithsonite powder and calcium carbonate powder and ball milled for 30 minutes, wherein the amount of smithsonite powder is 10% based on the weight of the potassium feldspar powder, and the amount of calcium carbonate powder is 8%.
[0053] Embodiment 7: This embodiment is based on Embodiment 5, and the difference from Embodiment 5 is that the potassium feldspar powder in this embodiment adopts modified potassium feldspar powder, and the specific preparation process of the modified potassium feldspar powder is as follows: Potassium feldspar powder and activated carbon powder are mixed for 60 minutes, and the amount of activated carbon powder is 5% based on the weight of the potassium feldspar powder; wherein the particle size of the activated carbon powder is smaller than the particle size of the potassium feldspar powder, and then the activated carbon powder is removed by screening, and then the potassium feldspar powder is mixed with smithsonite powder and calcium carbonate powder and ball milled for 30 minutes, wherein the amount of smithsonite powder is 10% based on the weight of the potassium feldspar powder, and the amount of calcium carbonate powder is 8%.
[0054] Comparative Example 1: This comparative example is based on Example 1, and the difference from Example 1 is that the formula does not contain nano clay and modified fiber reinforced polypropylene, specifically: A high-toughness concrete decorative brick, composed of the following components in parts by weight: 600 parts of ordinary Portland cement, 1200 parts of aggregate, 5 parts of polycarboxylate water reducer, and 180 parts of water.
[0055] In this comparative example, the water-to-binder ratio is.
[0056] Comparative Example 2: This comparative example is based on Example 1, and the difference from Example 1 is that the formula does not contain nano clay, specifically: A high-toughness concrete decorative brick, composed of the following components in parts by weight: 600 parts of ordinary Portland cement, 100 parts of modified fiber reinforced polypropylene, 1200 parts of aggregate, 5 parts of polycarboxylate water reducer, and 180 parts of water.
[0057] In this comparative example, the water-to-binder ratio is.
[0058] Comparative Example 3: This comparative example is based on Example 1, and the difference from Example 1 is that the formula does not contain modified fiber reinforced polypropylene, specifically: A high-toughness concrete decorative brick, composed of the following components in parts by weight: 600 parts of ordinary Portland cement, 150 parts of nanoclay, 1200 parts of aggregate, 5 parts of polycarboxylate water reducer, and 180 parts of water.
[0059] In this comparative example, the water-to-binder ratio is.
[0060] Comparative Example 4: This comparative example is based on Example 1, and the difference from Example 1 is that steel fiber is used to replace modified fiber reinforced polypropylene, specifically: A high-toughness concrete decorative brick, composed of the following components in parts by weight: 600 parts of ordinary Portland cement, 150 parts of nanoclay, 100 parts of steel fiber, 1200 parts of aggregate, 5 parts of polycarboxylate water reducer, and 180 parts of water.
[0061] Comparative Example 5: This comparative example is based on Example 1, and differs from Example 1 in that bentonite is used to replace nanoclay.
[0062] A high-toughness concrete decorative brick, composed of the following components in parts by weight: 600 parts of ordinary Portland cement, 150 parts of bentonite, 100 parts of steel fiber, 1200 parts of aggregate, 5 parts of polycarboxylate water reducer, and 180 parts of water.
[0063] Comparative Example 6: This comparative example is based on Example 1, and the difference from Example 1 is that: In the process of preparing the modified fiber reinforced polypropylene, no potassium feldspar powder is added.
[0064] Comparative Example 7: This comparative example is based on Example 1, and the difference from Example 1 is that in the process of preparing the modified fiber reinforced polypropylene, the amount of potassium feldspar powder added is different, specifically: In the process of preparing modified fiber reinforced polypropylene, the addition amount of potassium feldspar powder in the maleic anhydride grafted polypropylene is 10% based on the weight of the maleic anhydride grafted polypropylene.
[0065] Comparative Example 8: This comparative example is based on Example 1, and the difference from Example 1 is that in the process of preparing the modified fiber reinforced polypropylene, the amount of potassium feldspar powder added is different, specifically: In the process of preparing the modified fiber reinforced polypropylene, the addition amount of potassium feldspar powder in the maleic anhydride grafted polypropylene is 17% based on the weight of the maleic anhydride grafted polypropylene.
[0066] After the concrete prepared in Examples 1 to 7 and Comparative Examples 1 to 8 was hardened for 28 days, the compressive strength and elastic modulus of each concrete specimen were tested with reference to GB / T50081-2019, and the water permeability coefficient of each concrete specimen was tested with reference to GB / T25993-2010; the tensile strength of each concrete specimen was tested with reference to standard T / CECS 10107; and the fracture toughness of each concrete specimen was tested with reference to standard DL / T 5332-2005 using a three-point method (the specimen size was 200 mm×200 mm×1000 mm, the prefabricated cracks were generated by pre-embedded steel plates, and the crack length was controlled at 80 mm±2 mm). The results are shown in Table 1: Table 1
[0067] From the data in Table 1, we can see that: 1) The high-toughness concrete decorative bricks prepared by the present invention have a compressive strength of more than 140MPa, a tensile strength of more than 15MPa, and a fracture toughness of more than 30KJ / m 2 As mentioned above, the water permeability coefficient is less than 1.7 mm / s; that is, the high-toughness concrete decorative brick prepared by the present invention has both high compressive strength and high toughness, and has a good anti-permeability coefficient.
[0068] 2) The nanoclay and modified fiber reinforced polypropylene in the present invention both have a great influence on the fracture toughness of the prepared high-toughness concrete decorative bricks, and the modified fiber reinforced polypropylene has a greater influence. At the same time, the modified fiber reinforced polypropylene also has a great influence on the compressive strength of the high-toughness concrete decorative bricks.
[0069] 3) The potassium feldspar powder in the nanoclay of the present invention has a great influence on the fracture toughness of the prepared high-toughness concrete decorative bricks. Compared with the addition of pure bentonite, the nanoclay containing potassium feldspar powder and bentonite of the present invention significantly improves the fracture toughness of the high-toughness concrete decorative bricks.
[0070] 4) Compared with adding steel fiber, the high-toughness concrete decorative bricks prepared by adding modified fiber-reinforced polypropylene in the present invention have significantly improved compressive strength and fracture toughness, and at the same time, the water permeability coefficient is improved.
[0071] 5) In the process of preparing modified fiber reinforced polypropylene, whether potassium feldspar powder is added to maleic anhydride grafted polypropylene and the amount of potassium feldspar powder added will affect the compressive strength and fracture toughness of the prepared high-toughness concrete decorative tiles.
[0072] 6) Modified potassium feldspar powder can further improve the compressive strength and fracture toughness of concrete.
[0073] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A high-toughness concrete decorative brick, characterized in that: It includes the following components by weight: 500-600 parts of cement, 120-150 parts of nano clay, 80-100 parts of modified fiber reinforced polypropylene, 1000-1200 parts of aggregate, 3-5 parts of water reducer, 100-200 parts of water; The fibers used in the modified fiber reinforced polypropylene are glass fibers and carbon fibers; the polypropylene used in the modified fiber reinforced polypropylene is maleic anhydride grafted polypropylene, and potassium feldspar powder is added to the maleic anhydride grafted polypropylene; Wherein, the nano clay is a mixture of bentonite powder and potassium feldspar powder; The potassium feldspar powder is a modified potassium feldspar powder; the preparation process of the modified potassium feldspar powder is as follows: The potassium feldspar powder is mixed with activated carbon powder for 30-60 minutes, wherein the particle size of the activated carbon powder is smaller than that of the potassium feldspar powder, and then the activated carbon powder is removed by sieving, and then the potassium feldspar powder is mixed with smithsonite powder and calcium carbonate powder and ball milled for 30 minutes, wherein, based on the weight of the potassium feldspar powder, the amount of the smithsonite powder is 10%, the amount of the activated carbon powder is 5%, and the amount of the calcium carbonate powder is 8%.
2. The high-toughness concrete decorative brick according to claim 1, characterized in that: The weight ratio of the bentonite powder to the potassium feldspar powder is (3-4):
1.
3. The high-toughness concrete decorative brick according to claim 1, characterized in that: The preparation process of the modified fiber reinforced polypropylene is as follows: Firstly, the glass fiber and the carbon fiber are surface treated with nano-silicon dioxide respectively, and then the surface treated glass fiber and the carbon fiber are mixed, and then the mixed fibers are mixed with the maleic anhydride grafted polypropylene, and then the modified fiber reinforced polypropylene is obtained by extrusion process.
4. The high-toughness concrete decorative brick according to claim 1, characterized in that: The amount of the potassium feldspar powder added to the maleic anhydride grafted polypropylene is 12-15% by weight.
5. The high-toughness concrete decorative brick according to claim 1, characterized in that: The aggregate includes coarse aggregate and fine aggregate; the particle size of the coarse aggregate is (2.5-2.0) mm, and the particle size of the fine aggregate is (0.5-0.8) mm; the weight ratio of the coarse aggregate to the fine aggregate is 1:(0.5-0.6).
6. The high-toughness concrete decorative brick according to claim 1, characterized in that: The high-toughness concrete decorative brick also includes 30-50 parts of mineral admixture; the mineral admixture is a mixture of fly ash and slag powder, and the weight ratio of the fly ash to the slag powder is (2-3):
1.
7. A high-toughness concrete decorative brick according to any one of claims 1 to 6, characterized in that: The water-to-cement ratio of the high-toughness concrete decorative brick is (0.20-0.25).
8. The method for preparing the high-toughness concrete decorative brick according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1, preparing the modified fiber reinforced polypropylene: S11, firstly surface-treating the glass fiber and the carbon fiber respectively with nano-silicon dioxide; S12, mixing the glass fiber and the carbon fiber processed in step S11 at a weight ratio of 3:1, wherein the length of the glass fiber and the carbon fiber are both 15-20 mm; S13, dispersing the potassium feldspar powder in the maleic anhydride grafted polypropylene, then uniformly mixing the mixed fiber and the maleic anhydride grafted polypropylene, putting them into an extruder for extrusion molding, cooling, and pelletizing to obtain the modified fiber reinforced polypropylene; S2. Add the cement, the nanoclay, the aggregate and the water reducing agent in proportion into a forced mixer and dry mix the mixture at a speed of 35-45 r / min for 3-4 minutes. After adding water and fluidizing stirring for 3-4 minutes, add the modified fiber reinforced polypropylene and continue stirring for 4-5 minutes to obtain concrete. Pour the concrete into a mold and cure it to obtain high-toughness concrete decorative tiles.
9. The preparation method according to claim 8, characterized in that: The weight ratio of the mixed fibers in the modified fiber reinforced polypropylene to the maleic anhydride grafted polypropylene is (2-3): (3-5); based on the weight of the maleic anhydride grafted polypropylene, the amount of potassium feldspar powder added to the maleic anhydride grafted polypropylene is 12-15%.
10. The use of the high-toughness concrete decorative brick according to any one of claims 1 to 7, characterized in that: The products used for preparation include decorative walls or floors.
Citation Information
Patent Citations
Polypropylene composite material
CN105754207A
Toughening modified polypropylene and preparation process thereof
CN106893202A
Nanoclay-modified high-performance concrete as well as preparation method and application thereof
CN110218054A
Corrosion-resistant polypropylene material for pipelines and preparation method thereof
CN110669285A
High-compatibility reinforced modified polypropylene material and preparation method thereof
CN118852790A